Conditional Value at Risk Portfolio With Monte Carlo Control Variates - Maga, Fahmi Giovani; Sulistianingsih, Evy; Satyahadewi, Neva (Department of Mathematics, Universitas Negeri Gorontalo, 2025)
Stock investment is one of the instruments investors favor due to its potential for high returns, but the risks stemming from stock price volatility cannot be overlooked. Value at Risk (VaR) is commonly used as a standard approach to measure and manage these risks. However, VaR has limitations in handling extreme risks, making Conditional Value at Risk (CVaR) is a more effective choice. This research measures the application of CVaR to a portfolio of banking sector stocks in Indonesia using the Monte Carlo Control Variates (MCCV) technique, with the Indonesia Composite Index (ICI) as the control variable. The portfolio consists of stock of PT Bank Rakyat Indonesia Tbk (BBRI) and PT Bank Negara Indonesia Tbk (BBNI). The purpose of this research is to compare CVaR calculation results using Standard Monte Carlo Simulation (MCS) and MCCV simulations. The data used includes the daily closing prices of BBRI, BBNI, and ICI stocks for the period from March 1, 2023, to February 29, 2024. The VaR and CVaR calculated in this study are for one day. The results of the analysis show that the MCS CVaR values at 90%, 95%, and 99% confidence levels are 1.730%, 2.050%, and 2.569%, respectively, while the MCCV CVaR values at 90%, 95%, and 99% confidence levels are 1.400%, 1.662%, and 2.084%, respectively. These values indicate that using the ICI as a control variable has successfully improved risk estimation by utilizing the ICI as a control variable.